Development of personal area network (PAN) for mobile robot using bluetooth transceiver [compact disc] - 381124 Choo, Sui Hong (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2004